GENERA AMYGDALUS AND LOUISEANIA IN KAZAKHSTAN: DISTRIBUTION AND INTRODUCTION EXPERIENCE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The genera Amygdalus L. and Louiseania Carrière (Aflatunia Vass.) are of great practical importance as decorative, soil-reinforcing trees and shrubs, which are of interest as wild relatives of cultivated plants. Naturally, 4 species of the genus Amygdalus grow on the territory of Kazakhstan, one of which is listed in the Red Book of Kazakhstan, another one is A. communis L. in artificial forest plantations and the monotypic genus Aflatunia (Louisiana), which is represented by only one species of Louiseania ulmifolia (Franch.) Pachom., is also listed in the Red Book of Kazakhstan. Introductory tests of these species in culture in the collections of the Institute of Botany and Phytointroduction.
Keywords: Amygdalus L., Louiseania Carrière, range, introduction.